Suspended sediment dynamics in the Amazon River of Peru - Armijos, E. (2013)
The erosion and transport of sediments allow us to understand many activities of significance, such as crust evolution, climate change, uplift rates, continental processes, the biogeochemical cycling of pollutants and nutrients. The Amazon basin of Peru has contrasting physiographic and climatic characteristics between the Andean piedmont and the plains and between the north and south of the basin which is why there are 8 gauging stations located along the principal rivers of the Andean piedmont (Marañón, Huallaga, Ucayali) and the plain (Marañón, Tigre, Napo, Ucayali and Amazon rivers). Since 2003, the ORE-Hybam (IRD-SENAMHI-UNALM) observatory has performed out regular measurements at strategic points of the Amazon basin to understand and model the systems, behavior and long-term dynamics. On the Andean piedmont, the suspended yields are governed by a simple model with a relationship between the river discharge and the sediment concentration. In the plain, the dilution effect of the concentrations can create hysteresis in this relationship on a monthly basis. The Amazon basin of Peru has a sediment yield of 541 *106 t year−1, 70% comes from the southern basin.